Investigating Rupi Kaur’s selected poems: an analysis of figurative language - Ferawati Ferawati; Sultan Baa; Iskandar Iskandar (Center for Humanities and Innovation Studies, 2022)
This research describes figurative language in Rupi Kaur’s selected poem in her book of poems, Milk and Honey, The Hurting. This research focused on the type of speech found and then analyzed its meaning. This research used descriptive qualitative using the theory of figurative language by Keraf. The authors read selected poems and interpreted them. Then find out the type of Figurative language used and the meaning of the selected poems by Rupi Kaur, The Hurting. This research showed that Rupi Kaur combined some figurative languages in her poems. The result of analyzing poems found eight types of figurative language. Those figurative languages are simile, metaphor, personification, epithet, synecdoche (totem pro-parte and pars-prototo), metonymy, apophasis, and alliteration. The poet creating and using this figurative language is a way to express her ideas, feelings, and thoughts about rape, sex, and abuse